Bremsstrahlung radiation detection for small animal imaging using a CCD detector. Issue 5 (May 2016) - Spinelli, Antonello E.; Boschi, Federico
Highlights: Optical imaging of radioisotopes. Bremsstrahlung radiation images. Small animal optical imager based on CCD detector. Abstract: The use of optical methods for the detection of radionuclides is becoming an established tool for preclinical molecular imaging experiments. In this paper we present a set of proof of principle experiments showing that planar bremsstrahlung radiation images can be detected with an intensifying screen using a small animal optical imager based on charge coupled device detector. We develop a bremsstrahlung source using a 32 P-ATP vial placed in a Plexiglas box, the source with an intensifying screen on top was placed inside a small animal optical imaging system. Bremsstrahlung radiation images were produced with the 32 P-ATP source only and also with a pair of pliers placed between the source and the screen. We found that the pair of pliers absorption image matches the shape of the object. Spatial resolution measurements were not performed however, the bremsstrahlung image of the pliers show that the resolution is relatively poor due to a large penumbra effect. We conclude that it is possible to produce planar bremsstrahlung images using optical imaging devices.